2020
DOI: 10.21608/javs.2020.85567
|View full text |Cite
|
Sign up to set email alerts
|

Preparation And Characterization Of Natural Nano Hydroxyapatite From Eggshell And Seashell And Its Effect On Bone Healing

Abstract: The Objectives of the present study were undertaken to prepared hydroxyapatite powder from eggshell and seashell and convert them in Nano size. Hydroxyapatite (HA) is a biomaterial with osteoconductive properties and is prepared by the precipitation method. The properties of HA can be enhanced when the material is synthesized in the Nanoscale range to use in the mandibular bone of the rabbit to examine the influence of (HA) on bone healing.The eggshell and seashell were cleaned, and the phosphoric acid was add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Some trace elements do not modify the elementary crystallographic properties of HA but may improve the general biological performance of the material used for implants [ 141 ]. Alhussary et al applied nano-HA from seashells and eggshells to the damaged mandibular bone of rabbits and reasoned that HA obtained from eggshells has an improved osteoinductivity and porosity than the one obtained from seashells [ 142 ]. Furthermore, Waheed recommended that eggshell scaffolds have superior compressive strength, increased mineralization, and improved osteogenic differentiation potential compared to commercial HA [ 143 ].…”
Section: Ha-based On Natural Sources Used In Btementioning
confidence: 99%
“…Some trace elements do not modify the elementary crystallographic properties of HA but may improve the general biological performance of the material used for implants [ 141 ]. Alhussary et al applied nano-HA from seashells and eggshells to the damaged mandibular bone of rabbits and reasoned that HA obtained from eggshells has an improved osteoinductivity and porosity than the one obtained from seashells [ 142 ]. Furthermore, Waheed recommended that eggshell scaffolds have superior compressive strength, increased mineralization, and improved osteogenic differentiation potential compared to commercial HA [ 143 ].…”
Section: Ha-based On Natural Sources Used In Btementioning
confidence: 99%
“…However, plenty of research is available in the literature that used and reported the calcium carbonate derived biogenic waste in foods, cosmetics, and pharmaceutical industry by a simple direct method, which is out of the interest of the current review paper. There is also plenty of research in the literature that used the calcium carbonate derived biogenic waste as starting materials to obtain other calcium derivatives such as calcium citrate (Palacios et al, 2021), hydroxyapatite (Alhussary et al, 2020), and calcium lactate (Daengprok et al, 2002) for pharmaceutical and food industry applications.…”
Section: Cosmetic Pharmaceutical and Food Industrymentioning
confidence: 99%
“…Consequently, in recent times the valorisation of eggshells waste as an alternative raw material for production of value added-products is upsurging. For instance, eggshell waste has been used as an additive in calcium phosphate bio-ceramics [ 75 , 76 , 77 ], as calcium supplement [ 78 , 79 , 80 , 81 ], adsorbent material [ 57 , 82 , 83 ], as a solid catalyst for biodiesel production [ 84 , 85 , 86 , 87 ], bone graft substitute [ 28 , 88 , 89 , 90 ], environmental remediation [ 91 , 92 ], heavy metal removal [ 36 , 93 ]. However, the sole application of eggshells in food and industrial rely main on the calcite component for making fertilizer, medicines and building materials.…”
Section: Potential Uses Of Eggshellmentioning
confidence: 99%